An analysis of the changing social bases of America's political parties: Group support in the 2012 and 2016 presidential elections. (August 2019) - Zingher, Joshua N.
Abstract: In this note I address two questions: 1.) what were the group bases of the U.S. electoral coalitions in 2012 and 2016? 2.) how have the group bases of support changed in the past decades? I determine social group memberships significantly influence individual partisanship with a multivariate analysis using ANES data. I then measure how many votes each politically relevant social group contributed to the party coalitions in each presidential election between 1972 to 2016. I go on to discuss how group contributions have changed and discuss the demographic and behavioral forces driving these changes. The defection of college educated whites from the Republican Party to the Democratic Party was the most pronounced change from 2012 to 2016, but the Democratic Party's steadily increasing reliance on ethnic and racial minority groups remains the most important long-term trend. Overall, I find that the party coalitions in 2012 and 2016 were relatively stable and most changes were continuations of decades long trends, despite perceptions there has been a sudden realignment.